What is Football? Working on the Defects and Errors in Football - Abdiqaaxxorovich, Sharipov Odilbek (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, playing football allows you to develop physical qualities such as strength, speed, endurance, flexibility and agility. Football is an important tool in the mental and voluntary upbringing of the younger generation. Proper organization of football trainings and competitions has been shown to have a positive effect on cultivating such qualities as discipline, organization, aspiration, willpower, cheerfulness, diligence and making the right decisions.